Calculation of Costs of Pregnancy- and Puerperiumrelated Care: Experience from a Hospital in a Low-income Country (Journal of Health, Population and Nutrition, 2010)
Calculation of costs of different medical and surgical services has numerous uses, which include monitoringthe performance of service-delivery, setting the efficiency target, benchmarking of services across allsectors, considering investment decisions, commissioning to meet health needs, and negotiating revisedlevels of funding. The role of private-sector healthcare facilities has been increasing rapidly over the lastdecade. Despite the overall improvement in the public and private healthcare sectors in Bangladesh, lackof price benchmarking leads to patients facing unexplained price discrimination when receiving healthcareservices. The aim of the study was to calculate the hospital-care cost of disease-specific cases, specificallypregnancy- and puerperium-related cases, and to indentify the practical challenges of conducting costingstudies in the hospital setting in Bangladesh. A combination of micro-costing and step-down cost allocationwas used for collecting information on the cost items and, ultimately, for calculating the unit costfor each diagnostic case. Data were collected from the hospital records of 162 patients having 11 differentclinical diagnoses. Caesarean section due to maternal and foetal complications was the most expensivetype of case whereas the length of stay due to complications was the major driver of cost. Some constraintsin keeping hospital medical records and accounting practices were observed. Despite these constraints, thefindings of the study indicate that it is feasible to carry out a large-scale study to further explore the costsof different hospital-care services.Key words: Cost calculation; Costs and cost analysis; Health expenditure; Healthcare cost; Hospital cost;Maternal health; Micro-costing; BangladeshDOI: 10.3329/jhpn.v28i3.5555J HEALTH POPUL NUTR 2010 Jun;28(3):264-272